Influence of Natural Media Types on Growth and Development of Entompathogen Fungus Verticillium lecanii (Zimmermann) Viegas - Arie Hapsani Hasan Basri (Contributions of Central Research Institute for Agriculture, 2022)
The aims of this research are: (1). To find out the income of shallot farming in Wanasaba District, East Lombok Regency. (2). To determine the feasibility of shallot farming in Wanasaba District, East Lombok Regency. (3). To determine the behavior and structure of the shallot market in Wanasaba District, East Lombok Regency. The method used in this research is descriptive method. The research was conducted in Wanasaba District, East Lombok Regency in two villages, namely Wanasaba Village and Wanasaba Daya Village, based on the highest production volume purposive sampling, the unit of analysis used was producing farmers and marketing institutions involved in marketing shallots. A sample of 40 farmer respondents and 26 marketing agency respondents determined the number of respondents by quota sampling. Intake of respondents by accidental sampling for farmers and snowball sampling for marketing agencies. The type of data used is quantitative and qualitative data. Sources of data used are primary data and secondary data. The analytical method used for shallot farming and marketing in Wanasaba District is descriptive. The research results show that (1). The income of shallot farming in Wanasaba District, East Lombok Regency is IDR 21,978,644 per cultivated land area or IDR 115,677,073 per hectare per planting season. (2). Shallot farming in Wanasaba District, East Lombok Regency is economically feasible to cultivate because it has an R/C ratio >1. (3). The marketing behavior of shallots in Wanasaba District, East Lombok Regency, shows that price changes at the consumer level are perfectly transmitted to the farmer (producer) level with relatively efficient marketing margins in the second shallot marketing channel and a market structure that leads to high concentration oligopsony.